2011
DOI: 10.1002/per.801
|View full text |Cite
|
Sign up to set email alerts
|

What I do and What I think they Would Do: Social Axioms and Behaviour

Abstract: The social axioms system uniquely predicted a large variety of behaviours and preferences. It is suggested that (a) the assistance social axioms provide in predicting the behaviour of others, and (b) the self‐characteristics embedded in the axioms account for this unique prediction ability. Three studies, each pertaining to a different axiom, tested the prediction power of the social axiom regarding two types of behaviours: One that is directly impacted by how others are expected to behave, and another that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…Their relative importance and underlying mechanisms depend on the type of world views and self-views in relation to criterion variables. In Kurman's (2011) studies, social axioms were more predictive of behaviors that were logically affected by how others are expected to behave, whereas personal characteristics were more predictive of self-directed behavior. In the present research, mediation effects of self-views are found to vary depending on the specific social axiom.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Their relative importance and underlying mechanisms depend on the type of world views and self-views in relation to criterion variables. In Kurman's (2011) studies, social axioms were more predictive of behaviors that were logically affected by how others are expected to behave, whereas personal characteristics were more predictive of self-directed behavior. In the present research, mediation effects of self-views are found to vary depending on the specific social axiom.…”
Section: Discussionmentioning
confidence: 94%
“…World views and self-views are mutually dependent (Kurman, 2011). As Anaïs Nin (1961) put it, "We don't see things as they are, we see them as we are."…”
Section: Discussionmentioning
confidence: 99%
“…Even when cynical people face information and evidence that disconfirm their cynical beliefs, such as selfless acts, they still attribute these acts to self-interest (Critcher & Dunning, 2011). In an intergroup context, individuals with high social cynicism allocated more resources to ingroup rather than outgroup members (Kurman, 2011) suggesting that cynical beliefs is related to ingroup favoritism. Given their general mistrust of others, cynical people are more prone to negative perceptions of other human beings.…”
Section: Social Beliefs and Perceptions Of Group Prototypementioning
confidence: 99%
“…Of these, social cynicism is particularly relevant to intergroup contexts, as it refers to a negative view of human nature and lack of trust in general others, social institutions, and authority figures (Leung et al, 2002). In an interpersonal context, cynical beliefs bias individuals' assessment of others' motivation (Kruger & Gilovich, 1999) and are associated with lower interpersonal trust (Kurman, 2011;Singelis, Hubbard, Her, & An, 2003). Even when cynical people face information and evidence that disconfirm their cynical beliefs, such as selfless acts, they still attribute these acts to self-interest (Critcher & Dunning, 2011).…”
Section: Social Beliefs and Perceptions Of Group Prototypementioning
confidence: 99%
See 1 more Smart Citation